2019
DOI: 10.3390/v11111033
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Transcriptomic Comparison of the RNA Viromes of the Mosquito Vectors Culex pipiens and Culex torrentium in Northern Europe

Abstract: Mosquitoes harbor an extensive diversity of ‘insect-specific’ RNA viruses in addition to those important to human and animal health. However, because most studies of the mosquito virome have been conducted at lower latitudes, little is known about the diversity and evolutionary history of RNA viruses sampled from mosquitoes in northerly regions. Here, we compared the RNA virome of two common northern mosquito species, Culex pipiens and Culex torrentium, collected in south-central Sweden. Following bulk RNA-seq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(100 citation statements)
references
References 36 publications
7
93
0
Order By: Relevance
“…In agreement with previous virome studies, most of the taxa derived from honey-baited FTA cards have been identified in various invertebrates [39] and associated to mosquitoes [40]. Additionally, mosquito-specific viruses detected in FTA cards (Table 2) have been described as part of the viral communities harbored by several mosquito species in different geographic regions [41][42][43][44][45][46][47][48]. Bold type corresponds to the selected viruses for primers design.…”
Section: Virome Composition On Honey-baited Fta Cards During Entomolosupporting
confidence: 86%
See 1 more Smart Citation
“…In agreement with previous virome studies, most of the taxa derived from honey-baited FTA cards have been identified in various invertebrates [39] and associated to mosquitoes [40]. Additionally, mosquito-specific viruses detected in FTA cards (Table 2) have been described as part of the viral communities harbored by several mosquito species in different geographic regions [41][42][43][44][45][46][47][48]. Bold type corresponds to the selected viruses for primers design.…”
Section: Virome Composition On Honey-baited Fta Cards During Entomolosupporting
confidence: 86%
“…Besides invertebrate-related viruses, it was not surprising to find viral families usually detected in plants, fungi and algae (e.g., Tymoviridae, Totiviridae, Partitiviridae, Endornaviridae or Virgaviridae) as part of the viral diversity associated to honey-baited FTA cards ( Figure 1B). Since, in Culex mosquitoes, sequences related to Totiviridae-like viruses have been found in Guadeloupe [46], Australia [25], China [49] and California [41]; Partitiviridae-like viruses have been detected in Sweden [45,48], Australia [25], Kenya [49] and California [41]; Endornaviridae-like viruses in Australia [25] and Tymoviridae-like viruses have been identified in Guadeloupe [46], Kenya [49], California [41], China [53], and Sweden [48]. Moreover, a Culex Tymoviridae-like virus (CuTLV) that was isolated from a Culex spp.…”
Section: Virome Composition On Honey-baited Fta Cards During Entomolomentioning
confidence: 99%
“…Sequencing libraries, data generation and analysis was performed as previously described [37,72]. Briefly, ribosomal RNA (rRNA) was depleted from the total RNA extracts using the Ribo-Zero Gold (human-mouse-rat) kit (Illumina) following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Relative abundance was calculated as reads per million: that is, the number of reads mapped to a contig divided by the total amount of reads in a library multiplied by a million. A particular virus was considered abundant if (i) it represented >0.1% of total ribosomal-depleted RNA reads in the library, equivalent to a reads per million value of 1000 or more, and (ii) if the abundance was higher than that of the host COX1 gene [37,72]. If the relative abundance of a virus contig was less than 1 read per million mapped, or below the level of cross-library contamination due to index-hopping measured at 0.1% of the most abundant library for the respective virus species, the library was considered negative for the presence of the virus contig.…”
Section: Methodsmentioning
confidence: 99%
“…(class Arachnida) (Tassi et al, 2017;Freitas-Astua et al, 2018). Recently, a meta-transcriptomic approach on invertebrates expanded the diversity of nege-and nege-like viruses infecting or associated with mosquitos and flies (Webster et al, 2015(Webster et al, , 2016Shi et al, 2017;Medd et al, 2018;Sadeghi et al, 2018;Pettersson et al, 2019) and other invertebrates (Shi et al, 2016a;Debat, 2017;Feng et al, 2017;Nunes et al, 2017;Schoonvaere et al, 2018;Kondo et al, 2019). Nevertheless, there is still very limited information about the relationships between negeviruses and kitaviruses and also the evolutionary history of these two virus groups.…”
Section: Introductionmentioning
confidence: 99%